ECG signal compression using compressed sensing with nonuniform binary matrices - Ansari-Ram, F.; Hosseini-Khayat, S. (2012 16th CSI International Symposium on Artificial Intelligence and Signal Processing, 2012)
Wearable ECG sensors can assist in prolonged monitoring of cardiac patients. Compression of ECG signals is pursued as a means to minimize the energy consumed during transmission of information from a portable ECG sensor to a server. In this paper, compressed sensing is employed in ECG compression. To increase compression ratio and reduce distortion of the ECG signal, a non-uniform binary sensing matrix is proposed and evaluated.